Bradykinin B2 Receptor Signaling Increases Glucose Uptake and Oxidation: Evidence and Open Questions - Gregnani, Marcos Fernandes; Hungaro, Talita G.; Martins-Silva, Leonardo; Bader, Michael; Araujo, Ronaldo C. (Frontiers in Pharmacology, 2020)
The bradykinin B2 receptor (B2R) is classically involved in vasodilation and inflammatory responses. However, through the observation of hypoglycemic effects of ACE inhibitors, this protein has been related to metabolic glucose modulation in physiological and pathophysiological contexts. Although several studies have evaluated this matter, the different methodologies and models employed, combined with the distinct target organs, results in a challenge to summarize and apply the knowledge in this field. Therefore, this review aims to compile human and animal in order to provide a big picture about what is already known regarding B2R and glucose metabolism, as well to suggest pending investigation issues aiming at evaluating the role of B2R in relation to glucose metabolism in homeostatic situations and metabolic disturbances. The data indicate that B2R signaling is involved mainly in glucose uptake in skeletal muscle and adipose tissue, acting as a synergic player beside insulin. However, most data indicate that B2R induces increased glucose oxidation, instead of storage, via activation of a broad signaling cascade involving NO and PKG. Additionally, we highlight that this modulation is impaired in metabolic disturbances such as diabetes and obesity, and we provide a hypothetic mechanism to explain this blockade in light of literature data provided for this review, as well as other authors.